Context-aware multi-token concept recognition of biological entities - Kwangmin Kim; Doheon Lee (BMC Bioinformatics, 2021)
Abstract Background Concept recognition is a term that corresponds to the two sequential steps of named entity recognition and named entity normalization, and plays an essential role in the field of bioinformatics. However, the conventional dictionary-based methods did not sufficiently addressed the variation of the concepts in actual use in literature, resulting in the particularly degraded performances in recognition of multi-token concepts. Results In this paper, we propose a concept recognition method of multi-token biological entities using neural models combined with literature contexts. The key aspect of our method is utilizing the contextual information from the biological knowledge-bases for concept normalization, which is followed by named entity recognition procedure. The model showed improved performances over conventional methods, particularly for multi-token concepts with higher variations. Conclusions We expect that our model can be utilized for effective concept recognition and variety of natural language processing tasks on bioinformatics.